Comportamiento Epizootiológico de Parásitos Gastrointestinales Caninos Domésticos (canis familiaris) en el Barrio Brazales Parroquia Eloy Alfaro Cantón Latacunga - Malusin Punguil, Mayra Fernanda (2018)
The investigation on the gastrointestinal epizootiogical of parasitic behaviour in domestic dogs (canis familiaris) Brazales neigborhood it had like objective to determine the prevalence of the parasitics, according to the age, sex and breed of the canines through the flotation technique which it has been made coproparasitic laboratory exams using Sheather method where it has been determined the prevalence. One hundred fifty samples of stool were examined in the coproparasitological laboratory to verify the presence of infective eggs, taking into consideration that exist parasites that are zoonótico that infect the canine and the human being. So according the results were 64 result positive nematodes and protozoa for the prevalence of canines infected with parasite is the 43% and 86 result negatives corresponding to the 57%.With respect to the canines ages of 0-12 months, 40 samples analyzed, 21 correspond Ancylostoma that is 53%, 2 correspond to Áscaris. With the 5%, 9 correspond to Toxocara with the 23%, 3 correspond to Uncinaria with 8%, 5 correspond to Coccidia with 13%. To the 1- 5 years, 14 placas correspond to Ancylostoma with the 58% while the Áscaris correspond to 0%, 6 correspond to Toxocara with the 25%, 4 correspond to Uncinaria with the 17% while that Coccidia has 0%. Indicating a high level of infection; these data agree with the report in the studies carried out in the Galapagos island in what was observed a prevalence of 87,5%. However, reports of other countries showing low prevalences like the observed in Venezuela (5,5%), Argentina (52,4%) and EE. UU (Virgina) (33,6%).